SWOT and Strategy for The Development of Salt Industry in Sumbawa Regency - Probosari, Ninik; Ardhanariswari, Kartika Ayu; Wijayani, Ari (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study aims to find out how the strategy is in an effort to improve and develop people’s salt management in Sumbawa Regency. The problem faced is the problem of competitiveness and product added value which is still low, so that it leads to the level of the economic welfare of the economic actors in the salt sector. To overcome these problems, a Salt Development Strategy is needed in order to have competitiveness. SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is used in research to develop strategies by considering strengths and weaknesses (internal environment) as well as opportunities and threats (external environment) faced by the Regional Government of Sumbawa Regency in order to develop its salt potential. The method of data collection was carried out by the method of Focused Group Discussion, Participatory Resource Mapping, observation, interviews, and literature study. The research subjects are stakeholders in Sumbawa Regency, namely the Sumbawa Regency Government, Academics, Entrepreneurs/Industry, and Salt Farmers Community. This research is a type of qualitative descriptive research. The resulted of this research were the strategies to develop the salt industry. Those strategies were: 1). Increasing the salt business system financing program, 2). Facilitating group or institutional development through collaboration with related parties, 3). Education about salt innovation and technology, 4). Increased cooperation with the government, especially the Cooperatives, Trade, and UMKM Service and the Fisheries and Marine Service, 5). Strengthening institutional management through various human resources education and training, 6). Strengthening capital capabilities and business partnerships, 7). Improvement of supporting facilities and infrastructure, 8). Development of salt business through the introduction of side businesses supporting the salt industry and 9). Establishment of a salt business association in the context of sharing information and experiences related to the world of salt.